Parameters of functional abilities in running - research review - Radosav Đukić; Goran Bošnjak; Vladimir Jakovljević; Gorana Tešanović (University of Banja Luka, Faculty of physical education and sport, 2020)
Running as an athletic discipline requires a high level of endurance and speed endurance, which is directly related to the cardiovascular and respiratory systems, ie the ability of an athlete's body to withstand loads, and the following are listed as relevant factors for running success: anaerobic strength and maximum O2 consumption, lactic acid concentration and oxygen deficiency, ability to withstand stress, high ability to concentrate and its retention over longer periods of time. There is a lot of research that has studied the parameters of functional abilities in an attempt to find the most effective way to improve them, and since there are many similar and different data on this topic, this paper has been done to classify the available papsers by domestic and foreign authors which would lead to conclusions applicable both in practice and for further research. For the purposes of this research, original scientific papers have been analyzed that dealt with functional abilities as success factors in short, middle and long distance running and the impact of training on functional abilities, found in electronic databases - Medline, PubMed, Researchgate, Web of Science and Google Scholar. The research used in this review monitored transversely the values ​​of submaximal and maximal oxygen consumption, energy systems, heart rate values, pulmonary ventilation, blood lactate concentration, as well as their changes after longitudinal implementation of experimental protocols and training processes. Since the collected research had too few respondents from different populations with a small number of elite runners, and they did not have enough information about many years of experience, level of sports form, race categories, and descriptions of training and methods, obtaining empirical information based on evidence was limited, as well as reaching valid conclusions. Accordingly, there is a need for a more systematic approach to research and implementation of complex studies with a sufficient number of runners of all ages, both sexes of the elite level, and cooperation of academic researchers, clubs and athletes to enable studies that would provide significant statistics, analysis and interpretation. The results identified in this review provide a starting point for future research that identifies and quantifies predictors of functional performance as factors of short, middle, and long distance running success.